2016
DOI: 10.1016/j.ydbio.2016.02.027
|View full text |Cite
|
Sign up to set email alerts
|

Centroacinar cells: At the center of pancreas regeneration

Abstract: The process of regeneration serves to heal injury by replacing missing cells. Understanding regeneration can help us replace cell populations lost during disease, such as the insulin-producing β cells lost in diabetic patients. Centroacinar cells (CACs) are a specialized ductal pancreatic cell type that act as progenitors to replace β cells in the zebrafish. However, whether CACs contribute to β-cell regeneration in adult mammals remains controversial. Here we review the current understanding of the role of CA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
51
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(53 citation statements)
references
References 104 publications
1
51
1
Order By: Relevance
“…However, little is known about the presence of some salivary gland cells that could show a progenitor function. Interestingly, it has been reported that the CACs of the pancreas in adult mouse and zebrafish showed a progenitor function and may contribute to the maintenance of tissue homeostasis [31,32]. Similarly, we revealed the presence of centroacinar-like cells in the goat submandibular salivary glands and we hypothesize that cells could have a regenerative role.…”
Section: Discussionsupporting
confidence: 70%
“…However, little is known about the presence of some salivary gland cells that could show a progenitor function. Interestingly, it has been reported that the CACs of the pancreas in adult mouse and zebrafish showed a progenitor function and may contribute to the maintenance of tissue homeostasis [31,32]. Similarly, we revealed the presence of centroacinar-like cells in the goat submandibular salivary glands and we hypothesize that cells could have a regenerative role.…”
Section: Discussionsupporting
confidence: 70%
“…Repair and regeneration of the injured organ are orchestrated by many cell types including acinar cells, centroacinar cells, ductal cells, immune cells, and stellate cells 7, 8. The existence of a resident stem cell population in the organ remains controversial 9, 10.…”
mentioning
confidence: 99%
“…The majority of the exocrine tissue constitutes the acinar part of the gland (Houbracken & Bouwens, ), which is organized into pancreatic lobules, that is, acini (Geron, Schejter, & Shilo, ; Low, Shukla, & Thorn, ). The function of the acini is synthesis, storage, and secretion of digestive enzymes, for example, α‐amylases, lipases and proteases, and acinar fluid (Beer, Parsons, & Rovira, ; Leung & Ip, ). However, enzyme and fluid secretion are separate processes because secretion of fluid is dependent on movement of ions (chloride and sodium) and is related to osmotic flow of water from the cell into the duct.…”
Section: Introductionmentioning
confidence: 99%